Acute Metabolic Switch Assay Using Glucose/Galactose Medium in HepaRG Cells to Detect Mitochondrial Toxicity. Issue 1 (6th May 2019) - Kamalian, Laleh; Douglas, Oisin; Jolly, Carol E.; Snoeys, Jan; Simic, Damir; Monshouwer, Mario; Williams, Dominic P.; Park, B. Kevin; Chadwick, Amy E.
Abstract: Using galactose instead of glucose in the culture medium of hepatoma cell lines, such as HepG2 cells, has been utilized for a decade to unmask the mitochondrial liability of chemical compounds. A modified glucose‐galactose assay on HepG2 cells, reducing the experimental period for screening of mitochondrial toxicity to 2 to 4 hr, has been previously reported. HepaRG cells are one of the few cell lines that retain some of the important characteristics of human hepatocytes, offering advantages of working with a cell line, therefore, are considered an alternative for HepG2 cells in drug toxicity screening. A method is described here using HepaRG cells in an acute metabolic switch assay utilizing specific glucose/galactose media, a combined ATP‐protein‐LDH assay measuring three endpoints from one 96‐well plate, and a criteria to label a compound as a mitochondrial toxin. © 2019 by John Wiley & Sons, Inc.